Desenvolvimento de processo não-convencional para produção de celulases por Aspergillus niger em biorreator pneumático na presença de bagaço de cana-de-açúcar - Cunha, Fernanda Marisa da (Universidade Federal de São Carlos, 2011)
In Brazil, sugarcane bagasse stands out as an abundant and available source of lignocellulosic material in sugar mills. It has structural features that make it a possible inducer for cellulase production by microorganisms. Since sugarcane bagasse is a promising material both as an inducer of cellulases and as a feedstock for second generation ethanol, the development of innovative fermentation processes for the production of cellulases in industrial scale is necessary in order increase the viability of the enzymatic hydrolysis of this material. In this way, the purpose of this study was the development of an unconventional process for cellulase production using an Aspergillus niger strain. The process has the purpose of sugarcane bagasse utilisation as substrate for the production of an inoculum with first step of preparation in solid-state fermentation (SSF), besides its use as an inducer for the synthesis of cellulases by submerged fermentation (SF) in the presence of solids, operating in triphasic systems. With this aim, the effect of carbon source used, glucose (10 g.L-1 and 20 g.L-1) and lactose (10 g.L-1) and the type of inoculum preparation (conventional or inoculum first step in SSF) were evaluated in shaken flasks cultures. The best production of endoglucanase (CMCase) obtained in shaken flasks was 1052 ± 34 IU L-1, after 72 h in cultures and prepared with the inoculum with solid state fermentation as first step with solid medium supplemented with 10 g.L-1 of glucose. These results were validated in a pneumatic bioreactor of 5.0 L at different pH values (5.0 and 6.0). The best results obtained in terms of volumetric productivity were 57±13 U.L-1.h-1 of endoglucanase, 327±17 UL-1.h-1 of xylanase and 10±1 UL-1.h-1 of filter paper activity (Fpase) in cultures with pH 5.0 and unconventional inoculum. It can be stated that the production of cellulases in the presence of sugarcane bagasse with large particle size (1 to 2 mm) is a viable and promissing alternative. The unconventional inoculum proposed as the object of study, with first step in SSF, was superior to conventional inoculum, since when applied to fermentation systems resulted in 3-fold superior enzymatic productivity of CMCase. It can be stated either that studies with pH values that favor cellulases syntesis instead of proteases can increase significantly the volumetric productivity.
Keywords: Engenharia bioquímica; Enzimas; Fermentação; Bagaço de cana; Biorreatores pneumáticos; ENGENHARIAS::ENGENHARIA QUIMICA